Theoretical Analysis of the Impact of Deviations in the Magneto-Rheological Damper Axis from the Runner Axis in the Butt of a Firearm During a Shot - Marcin BAJKOWSKI (Analiza teoretyczna wpływu kąta odchylenia osi tłumika magnetoreologicznego od osi prowadnic w kolbie na jego działanie podczas strzału, 2017)
This paper presents a method of modelling the impact of a magneto-rheological (MR) butt-mounted damper on both the weapon and the shooter during the use of a firearm. A modification of the model presented in [1] is suggested. The study focused on determining the impact of deviations of the MR damper axis from the runner axis in the butt during recoil, especially on the energy dissipated. Sample results are presented for the analysis of a smoothbore hunting weapon, calibre 12/70. The results demonstrate that the size of this angle has no significant impact on the course of the recoil nor on dissipation of the recoil energy. Therefore, in weapon design practice, there is no justification for implementing constructional solutions in the butt enabling adjustment of the MR damper deviation axis from the runner axis.
Keywords: Oddziaływanie tłumika broni strzeleckiej na proces strzału